Connecting the Ancient West and East (Leuven ; Paris ; Bristol)
2 cilt (1. c. xliv, 904 sayfa ; 2. c. x sayfa, sayfa [905]-1525)
Keywords: “Connecting the ancient West and East has been the life’s goal of the Georgian-born scholar Gocha Tsetskhladze since he stepped westward from the then Soviet Union in 1990 (his higher education took place in Kharkov and Moscow). This publication honours his not inconsiderable achievements, following in (and filling) the footsteps of Minns and Rostovtzeff, unremittingly for 30 years, first in Oxford, then London and Melbourne, now in Wales. Its publication occurs just short of his sixtieth birthday. Epithets applied to him have included ‘king of Pontus’ and ‘Mr Colonisation’, for his focus has been the Black Sea and Greek colonisation, unashamedly called that, of its coasts, and the exploration of Graeco-native contacts there and in the related hinterland, starting first from his native Colchis, where the Greeks learnt a thing or two from the locals : two-way exchange, not unidirectional Hellenisation. More recently, his attention turned to excavation of Pessinus in Central Anatolia. The work is divided into two volumes : the first focused primarily on the Black Sea; the second spreading its wings to other regions. Over a hundred scholars, based predominantly in Europe, North America and Australia, have contributed 85 papers and several personal reminiscences.” --